PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN KEAKTIFAN BELAJAR PESERTA DIDIK PADA KELAS V SD NEGERI - Susanti, Ratih; Stavinibelia, Stavinibelia (Biro 3 Kemahasiswaan dan Kerjasama Universitas Abduracman Saleh Situbondo, 2024)
This research study aims to determine the increase in student learning activity by applying a project-based learning model in learning on the material of economic activity objects, people and objects in the environment in class V SDN 01 Ulak Karang. This research is a Kemmis & MC Taggart model classroom action research using a project-based learning model implemented in II cycles. The subjects in this study were the fifth grade students of SDN 01 Ulak Karang Selatan, which amounted to 28 people. Consisting of 16 male students and 12 female students. The students' activities were measured from the students' observation sheets, students' learning activity sheets, and LKPD sheets for each pre-cycle or each session. From the results of the study, it is known that the project-based learning model can increase student activeness in the thematic learning process in class V SDN 01 Ulak Karang Selatan. Project-based learning can improve the results of student activeness seen from the pre-cycle. Initial observations obtained a percentage of 2.6% with a less active category, in cycle I with a percentage of 3% with a fairly active category, in cycle II experienced an increase with a percentage of 4.1% with an active category. In Cycle II, it can be seen from the pre-cycle that there was a better increase in student activeness so that it reached a percentage of 4.1% in the active category.